Mechanisms of Economic Growth - V. V. Ivanter (Мир новой экономики)
The article is devoted to the mechanisms of economic growth. It examines the role and place of strategic planning in the economic policy of theRussian Federation. It also shows the important role of increasing demand and investment — the main engines of economic growth. The purpose of the article is a presentation of the proposal of priority steps for the launch of the stable development of the Russian economy. The article states that a favourable macroeconomic situation in the country is a necessary but not sufficient condition for economic growth, and shows the main factors that limit it. To achieve these goals, the authorities need to provide an active economic policy based on strategic planning. The adopted government program of digitalization can accelerate the growth of the economy, but will not automatically improve its structure. It is concluded that it is necessary to increase the rate of accumulation (investment) and ensure productivity growth. This requires modernization of production, improvement of labour organization, development of education and career guidance, increase of working life, as well as replication of successful experience. To solve the main task of economic development, it is proposed to introduce infrastructure bonds and project financing more actively, to support exports and to use other incentives. A successful transition to projectbased public administration is also needed.